The mechanics of the circulation - Caro, Colin G. (Colin Gerald) (Cambridge, UK ; New York : Cambridge University Press, 2012)
"Continuing demand for this book confirms that it remains relevant over 30 years after its first publication. The fundamental explanations are largely unchanged, but in the new introduction to this second edition the authors are on hand to guide the reader through major advances of the last three decades. With an emphasis on physical explanation rather than equations, Part I clearly presents the background mechanics. The second part applies mechanical reasoning to the component parts of the circulation: blood, the heart, the systemic arteries, microcirculation, veins and the pulmonary circulation. Each section demonstrates how an understanding of basic mechanics enhances our understanding of the function of the circulation as a whole. This classic book is of value to students, researchers and practitioners in bioengineering, physiology and human and veterinary medicine, particularly those working in the cardiovascular field, and to engineers and physical scientists with multidisciplinary interests"--
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Hemodynamics; Blood -- Circulation; Mathematics